Affective spaces: a praxeological outlook - Reckwitz, Andreas (Rethinking history, 2012)
Classical social and cultural theory disregards the spatial and affective dimensions of social phenomena because of its anti-technological and anti-aesthetic bias. The first part of my paper digs into the reasons for this ignorance. Against this background, the second part outlines an alternative conceptual proposal, which I label a praxeological perspective. This approach offers a framework for analysing emotions and affects that simultaneously pays attention to artefacts and to space. It integrates all of these as basic components of sociality and, by doing so, avoids both the pitfall of their complete culturalisation and that of their total naturalisation. The aim is to achieve a basic 'aesthetisation' and 'materialisation' of cultural theory, instead. The third part, finally, illuminates the interconnection between emotions and space and argues that in order to explain the cultural change of affective structures in history, the analysis of the emergence of new artefact-space complexes is indispensable.